2021
DOI: 10.1002/pri.1899
|View full text |Cite
|
Sign up to set email alerts
|

Home‐based multimodal exercise program in older people with Alzheimer disease: Randomized controlled trial protocol

Abstract: Background At‐home physical exercise may be an important intervention strategy for older people with Alzheimer disease (AD) due to the greater adherence and ease for the caregivers. Purpose Determine the effects home‐based multimodal exercise program in older people with AD on muscle strength, balance, functioning, cognition, dual task performance, frailty, and physical activity level. Methods This is a trial with 40 older people with mild and moderate AD, randomized into intervention group (IG) and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Dance intervention had a positive effect on performance of physical function, decreased the rate of falling, and increased the balance among older adults (Liu et al, 2021;Mattle et al, 2020;Zhao et al, 2021). Previous studies also showed that regular exercise can relieve negative emotions, improve sleep quality, and lead to significant improvements in cognitive function (Cezar et al, 2021;Cheng et al, 2021). Furthermore, despite the proximity of families, loneliness and social isolation negatively affect the quality of life among older adults living in communities.…”
Section: Discussionmentioning
confidence: 96%
“…Dance intervention had a positive effect on performance of physical function, decreased the rate of falling, and increased the balance among older adults (Liu et al, 2021;Mattle et al, 2020;Zhao et al, 2021). Previous studies also showed that regular exercise can relieve negative emotions, improve sleep quality, and lead to significant improvements in cognitive function (Cezar et al, 2021;Cheng et al, 2021). Furthermore, despite the proximity of families, loneliness and social isolation negatively affect the quality of life among older adults living in communities.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, the informal caregivers had minimal exercise experience and facilitated the exercise intervention to their loved ones as opposed to an exercise professional, with only weekly remote supervision by a research assistant. To our knowledge, only three RCTs of home-based exercise in people with dementia used SPPB as an outcome and one RCT is currently pending results ( Cezar et al, 2021 ). The two completed RCTs ( Callahan et al, 2017 ; Pitkälä et al, 2013 ) reported no improvements in the SPPB.…”
Section: Discussionmentioning
confidence: 99%
“…The LAPESI telehealth protocol, inspired by a home‐based exercise program for patients with Alzheimer's disease (AD‐HOMEX), is a protocol designed by our research group for use in the home setting that has been tested in a registered clinical trial (RBR‐2mhvwv) (Cezar, Ansai & Andrade, 2021; Cezar et al., 2021; Cezar et al., 2021, 2021). It is important to point out that some adaptations were made to be carried out remotely, especially regarding the intervention time and safety precautions described ahead below.…”
Section: Methodsmentioning
confidence: 99%